Multi-indicator Systems and Modelling in Partial Order - Brüggemann, Rainer; Carlsen, Lars; Wittmann, Jochen (Springer eBooks, 2014)
"Multi-indicator Systems and Modelling in Partial Order" contains the newest theoretical concepts as well as new applications, and applications where standard multivariate statistics fail. Some of the presentations have their counterpart in the book; however, there are many contributions, which are completely new in the field of applied partial order.